On the Dynamics of Gasoline Market Integration in the United States: Evidence from a Pair-wise Approach - Mark J. Holmes; Jesús Otero; Theodore Panagiotidis (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper employs a pair-wise approach to examine regional integration in the US gasoline market. Using gasoline price data at the state level over a period of more than two decades, we find strong support for the view that the law of one price holds in regional markets, as more than 80% of bivariate price differentials turn out to be stationary. Furthermore, we uncover evidence that the speed at which prices converge to the long-run equilibrium depends upon the distance between states. Asymmetries are also present in this relationship. Our findings suggest that the more similar are states with respect to taxation, gas stations and refining capacity, the faster is the speed of adjustment towards the long-run equilibrium.
Keywords: C33; Q47; R11; 330; Panel data; pair-wise approach; market integration; gasoline; speed of adjustment; Benzinpreis; Preiskonvergenz; Marktintegration; Panel; USA